Non-Hodgkin lymphoma of sinuses and nasal cavity: case series of two - Dalmia, Deepak; Behera, Sanjaya Kumar; Bhatia, Jas Simran Singh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Non-Hodgkin lymphoma is a type of hematologic malignancy derived from lymphocytes, which varies significantly in their severity, from slow growing to very aggressive types. Incidence increases with age. Up to 45 years of age Non-Hodgkin lymphoma is more common among males than females. Various etiological factors includes infectious agents like Epstein-barr virus, Human T-cell leukemia virus, Helicobacter pylori, Human herpes virus-8, Hepatitis c virus, HIV etc. Exposure to chemical like polychlorinated biphenyls, phenoxy herbicides and medical treatments like radiation therapy and chemotherapy also act as etiological factors. Genetic diseases like Klinefelter’s syndrome, ataxia telangiectasia and autoimmune diseases like celiac sprue, rheumatoid arthritis and systemic lupus erythematosus can also act as causal factors. NHL in nose and nasal cavity is a rare finding. Ours is a case series of two rare case of non-Hodgkin lymphoma presented with a nasal mass with nasal obstruction. The first case is a sixty years old female patient who presented with a right nasal mass with nasal obstruction. The second case is a fifty years old male who presented with left side nasal mass with left proptosis. We diagnosed these cases by taking biopsy from the nasal masses. These cases highlighted the importance of good clinical history and examination along with management according to definite protocols in regarding to avoid missing a rare.